Sexualities in Victorian Britain - Andrew Miller, James Adams (Indiana University Press, 1996)
"This book promises to lay to rest, once and for all, the early 20th-century truism that Victorians' primary relationship to sexuality turned on repression." -Mary L. Poovey, Johns Hopkins University An introduction to Victorian sexualities and a survey of current critical methods, these essays will energize reflection on the complexity of human sexuality and on the many different arrays of meaning that it has generated. Contributors are James Eli Adams, Joseph Bristow, Jonathan Dollimore, Margaret Homans, Rosemary Jann, Andrew H. Miller, Thaïs E. Morgan, Ornella Moscucci, Deborah Epstein Nord, Camilla Townsend, Herbert F. Tucker, and Martha Vicinus.